2009
DOI: 10.1557/jmr.2009.0294
|View full text |Cite
|
Sign up to set email alerts
|

A new viewpoint to the mechanism for the effects of melt overheating on solidification of Pb-Bi alloys

Abstract: The effects of melt overheating treatment on solidification of Pb-Bi alloys were studied from the viewpoint of liquid-liquid structure change (LLSC). Anomalous temperature dependence of internal friction, electrical resistivity, and entropy of liquid Pb-Bi alloys suggested that discontinuous LLSC occurred within about 520–740 °C, based on which the solidification experiments were carried out with different states of Pb-Bi melts. The results revealed that the LLSC affected the solidification behavior and micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…After all, if Bi forms a liquid crystal over a wide range of temperatures, this type of ordering would not be immediately destroyed by admixture of other elements. In a study [16] of an 80%Bi-20%Pb alloy, an irreversible transformation was observed above 800 K, with a particularly striking signature in the thermopower data (see their Fig. 2).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…After all, if Bi forms a liquid crystal over a wide range of temperatures, this type of ordering would not be immediately destroyed by admixture of other elements. In a study [16] of an 80%Bi-20%Pb alloy, an irreversible transformation was observed above 800 K, with a particularly striking signature in the thermopower data (see their Fig. 2).…”
mentioning
confidence: 94%
“…Finding a liquid-crystal phase to be thermodynamically stable in an elementary melt, even over only a very limited range in temperature and pressure, would be a revolutionary change in our understanding of the phase diagrams of the elements. If the range of stability of liquid-crystal phases in simple melts is much wider (Sb and Sn are additional candidates [31,32,11,29]), then this could serve as a basis for solving many of the riddles in the field of liquid-liquid transformations, and would likely have significant technological implications as well [16].…”
mentioning
confidence: 99%
“…PbSn, InSn, CuSn and SnBi [3][4][5][6][7]. Further works also reveal that the LLSC has significant impact on the solidification process and properties of alloys [8][9][10][11][12]. All of these studies promoted our knowledge about the nature of liquid structure and the correlation of liquid-solid.…”
Section: Introductionmentioning
confidence: 82%
“…More recently, both experimental findings and theoretical predictions have suggested the presence of liquid-liquid structural transitions (LLST) characterized by significant structural changes [13][14][15][16]. Furthermore, according to the known melt structure information, the effect of the LLST on the solidified structures was investigated for some binary alloys, such as Al-Si [2], Pb-Sn [17], Bi-Sb [18] and Pb-Bi [19].…”
Section: Introductionmentioning
confidence: 99%